A topology on BCK-modules via prime sub-BCK-modules - T. Roudbari; N. Motahari (Journal of Hyperstructures)
In this paper, by considering the notion of prime BCKsub-modules of BCK-modules, we introduce a topology on prime BCK-sub-modules of BCK-modules. Moreover, the notion of top BCK-modules, semi-prime sub -BCK-modules and extraordinary sub- BCK-modules are introduced. Finally the relationships between them are studied.